Hukum Kesehatan dalam Perspektif Filsafat Hukum - Mardianti, Alis; Adam, Faisal; Maisyaroh, Sitti; Fitria, Fitria; Sapsudin, Asep (Syntax Literate, 2025)
Health law is a field that has a strategic position in ensuring the protection of human rights, especially in the context of modern health services that continue to develop. The development of medical technology, improving the quality of services, and strengthening the rights of patients have increasingly complex ethical, moral, and regulatory implications. This study aims to analyze health law from the perspective of legal philosophy by reviewing the concepts of values, principles of justice, equality, and morality that are the foundation of its regulation. Through a theoretical approach, this study discusses how health law is positioned as a system of norms that protect patients, direct the practice of health workers, and balance the relationship between professional obligations and the interests of society. In addition, the analysis is focused on the application of health law in daily life, including service ethics, patient rights, medical confidentiality, and legal protection mechanisms through regulations such as the Health Law No. 17 of 2023. The results of the study show that strengthening professional ethics, the integrity of health workers, and the legal system that favors patient safety is the key to improving the quality of health services. Thus, health law not only functions as a regulatory instrument, but also as a moral and philosophical pillar in maintaining human dignity and the quality of health services.